Portable data acquisition system / Nik Musalmah Mostafa - Mostafa, Nik Musalmah (1994)
A portable data acquisition system package is developed based on a microcontroller. The microcontroller is a complete solution for control and data collection applications where no external computer logic, external analog signal conditioning or other special hardware is needed. The microcontroller has eight input channels and one output channel. This allows connection to a variety of sensor devices such as temperature and pressure. By using portable data acquisition system, we do not need to bring PC to the field to collect data. All the data can be stored into the battery backed RAM. In either case, the program will automatically execute on reset or power up and it is no longer necessary to have a PC connected to it. The microcontroller was connected to the serial port of the PC for software development. The language used to program the system is C. Once the task required has been programmed, the program can be burned into the EPROM for permanent installation on the microcontroller board.